Zsidóellenes törvényhozás német-magyar összehasonlításban - Abram, Helen Ahlke (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Legislation in the 1930s and 1940s in both Germany and Hungary was characterised by anti-Semitic ideas of ‘racial protection’. Against this background, the underlying thought patterns and the mutual influence of the two countries’ legislation are discussed in research literature. Nevertheless, no detailed comparison of the relevant German and Hungarian regulations exists to date. This article therefore looks for parallels that existed between German and Hungarian anti-Jewish laws. To this end, an overview of the relevant German ‘racial legislation’ is first given, before the Hungarian anti-Jewish laws, which are the focus of the analysis, are presented. Finally, a comparison is made between the German and Hungarian legislation.